2000
DOI: 10.1002/(sici)1527-2648(200004)2:4<184::aid-adem184>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Cellular Magnesium Materials

Abstract: Especially cellular aluminum materials have been extensively developed and investigated in the recent years. But also magnesium is a suitable metal for cellular metals due to its low density. By a special casting method open‐cellular magnesium with a very low density of 0.05 g/cm3 is fabricated that shows high potential for usage as energy absorbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 7 publications
1
25
1
2
Order By: Relevance
“…Changing the pore size, pore shape, porosity, and pore distribution can affect the mechanical properties [48,83,84]. Increasing porosity results in the decrease of compression strength, yield strength, and Young's modulus [48,83,84].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Changing the pore size, pore shape, porosity, and pore distribution can affect the mechanical properties [48,83,84]. Increasing porosity results in the decrease of compression strength, yield strength, and Young's modulus [48,83,84].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Increasing porosity results in the decrease of compression strength, yield strength, and Young's modulus [48,83,84]. The mechanical properties of porous magnesium prepared by the green compacts method using carbamide particles as the space holder and under 100 MP uniaxial pressure were studied to demonstrate the dependence of mechanical properties on pore size and porosity [48].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Echigo et al have shown that the minimum required heating value of the gas to sustain combustion in the ceramic foam is roughly around about 10-50 kWh/m 2 , while the maximum generated power was 226 Wh/m 2 in this experiment. These results imply that once we could control the volumetric surface areas of the porous thermoelectric elements by using novel fabrication techniques, such as evacuation casting into the open cellular mold, 20) unidirectional solidification, 21) it would become feasible to increase the conversion efficiency to those theoretically predicted.…”
Section: Discussionmentioning
confidence: 99%
“…During both, the plastic pattern is degraded endothermically and replaced by liquid metal (Figure 9). Polyurethane [38] or epoxy [39] foam with gating system, for example, made of wax, is placed at the mold bottom and plaster is poured into it. The plaster-polymer composite is heated to 500-700 C to burn out the plaster and evaporate the foam.…”
Section: Pattern Castingmentioning
confidence: 99%
“…Preform infiltration Density [g cm À3 ] 0.39-0.57 [32]a) 0.15-0.89 [85] Compressive strength [MPa] 13-15 [29] , 1.2-2.5 [32]a) 0.27-0.51 [85] Pattern casting Density [g cm À3 ] >0.05 [38]e) 0.16-0.25 [86] www.advancedsciencenews.com www.aem-journal.com production method and parameters. Porosities obtained in GASAR processes are connected with hydrogen solubility in liquid metal.…”
Section: Propertiesmentioning
confidence: 99%